(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The article is devoted to the possibility of renovation of Diedrichson Street in order to create a public space taking into account all the existing problems of the street and the adjacent territories of educational institutions. The main idea of the article is: creation of a pedestrian zone on the basis of modern campuses of the world. Introduction of new functions on the territories of educational institutions, competent development of urban planning and architectural-planning structure through renovation and rehabilitation of territories, which will lead to the influx of students and will be a calling card for all institutions located along Diedrichson Street. The article presents the peculiarities of the design and renovation of pedestrian zones and streets, identifies the main problems of the street and the neighbourhood, provides solutions to solve them, identifies the advantages of the historical student quarter. Examples of projects of student campuses and pedestrian streets in the world experience are given. As a result of reconstruction the pedestrian zone of Diedrichson Street in the centre of Odessa can become the centre of social life of the institute campus, due to such improvements as: creation of unique design of student space; development of cultural environment; development of public infrastructure; modern landscaping of the territory - creation of a single "green zone", which will connect all educational institutions. It also explores the possibility of creating a new attraction in Odessa, which will attract not only students and teachers, but also just visitors to the new space, which will probably become one of the new centres of popularisation of education and culture. The main result of the article is the organisation of an inclusive entrance to the AHI building of OSAEA from Diedrichson Street.